Racial Reconciliation and Privilege The Debate Within the Seventh-Day Adventist Church on Regional Conferences - Hector, Winsley B. (Claremont Dissertations of Distinction, 2017)
This volume examines the history of racial policies in the Seventh-Day Adventist Church.